2012
DOI: 10.1155/2012/127430
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Impact of n-Decane, Decalin, and Isoparaffinic Solvent on Elastomeric Sealing Materials

Abstract: One of the crucial aspects in the adoption of alternative fuels (e.g., GtL fuel) in aviation industry is to investigate their compatibility with elastomeric materials used in current gas turbine engines. This study employed stress relaxation technique to investigate the effects of three solvents, namely, decalin (cycloparaffin), n-decane (normal paraffin), and ShellSol T solvent (isoparaffins) on O-rings made from different materials. Results indicated that both fluorosilicone and fluorocarbon O-rings showed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Aqueous phase hydrodeoxygenation was performed on the substituted diphenylmethane products over Pd/C and HZSM-5 (Scheme 35). After vacuum distillation, the expected dicyclohexylmethane (24) [309] was observed in the reaction mixture as the minor product (31.4 %), while the intramolecular cyclization product, perhydrofluorene (25), was obtained as the major product (68.6 %). The density of pure dicyclohexylmethane is 0.88 g mL À 1 ,while perhydrofluorene has a density of 0.96 g mL À 1 at 20°C.…”
Section: Lignin-derived Phenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aqueous phase hydrodeoxygenation was performed on the substituted diphenylmethane products over Pd/C and HZSM-5 (Scheme 35). After vacuum distillation, the expected dicyclohexylmethane (24) [309] was observed in the reaction mixture as the minor product (31.4 %), while the intramolecular cyclization product, perhydrofluorene (25), was obtained as the major product (68.6 %). The density of pure dicyclohexylmethane is 0.88 g mL À 1 ,while perhydrofluorene has a density of 0.96 g mL À 1 at 20°C.…”
Section: Lignin-derived Phenolsmentioning
confidence: 99%
“…Recent work has shown that cycloalkanes at concentrations above about 30 vol % in SPKs have swelling characteristics similar to conventional jet fuel. [24][25][26] This result has opened up the development of aromatic-free bio-based fuels with increased gravimetric heats of combustion and improved emission profiles. [27] Bio-based cycloalkanes represent the missing link to the production of full-performance and ultra-performance drop-in synthetic fuels for commercial and military jet aircraft.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9,10 ] In addition, recent research has suggested that cycloalkanes can potentially be used to replace aromatic compounds in SAF blends, improving gravimetric NHOC and reducing particulate emissions, while maintaining the essential seal‐swelling properties exhibited by conventional jet fuels. [ 11–14 ]…”
Section: Introductionmentioning
confidence: 99%
“…The importance of aromatic components in jet fuel pertain to their ability to aid in overall lubricity and seal swell (13)(14)(15)(16) . This is imperative to maintain the integrity of the aircraft's fuel system.…”
Section: Introductionmentioning
confidence: 99%